2017
DOI: 10.1093/jxb/erx324
|View full text |Cite
|
Sign up to set email alerts
|

A light-sensitive mutation in Arabidopsis LEW3 reveals the important role of N-glycosylation in root growth and development

Abstract: Plant roots have the potential capacity to grow almost indefinitely if meristematic and lateral branching is sustained. In a genetic screen we identified an Arabidopsis mutant showing limited root growth (lrg1) due to defects in cell division and elongation in the root meristem. Positional cloning determined that lrg1 affects an alpha-1,2-mannosyltransferase gene, LEW3, involved in protein N-glycosylation. The lrg1 mutation causes a synonymous substitution that alters the correct splicing of the fourth intron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…However, the majority of these analyses were done with the root system growing in the presence of light. We previously showed that root illumination generates a stress (Silva‐Navas et al ., , ; Manzano et al ., ). In this work, we demonstrate that illumination is an additive stress to Pi starvation.…”
Section: Discussionmentioning
confidence: 97%
“…However, the majority of these analyses were done with the root system growing in the presence of light. We previously showed that root illumination generates a stress (Silva‐Navas et al ., , ; Manzano et al ., ). In this work, we demonstrate that illumination is an additive stress to Pi starvation.…”
Section: Discussionmentioning
confidence: 97%
“…A genetic screen to identify plants with an altered root system was carried out using an EMS‐mutagenized SKP2Bp::GUS marker population (Manzano et al ., , ). Mutants displaying root development defects or altered expression of SKP2B (S‐phase kinase‐associated protein 2) were identified.…”
Section: Resultsmentioning
confidence: 99%
“…Glycosyltransferases perform N-glycosylation, a post-translational protein modification involved in various biological processes [ 24 27 ]. N-glycosylation plays a positive role in the development of the cell wall [ 24 ], leaves [ 25 ], and roots [ 26 ]. α - 1,2-Glucosyltransferase (ALG10) is a key enzyme that participates in the final step of liposaccharide formation, catalyzing the transfer of the last glucosyl molecule to a liposaccharide precursor to generate oligosaccharide chains in the N-glycan biosynthesis pathway [ 28 ].…”
Section: Introductionmentioning
confidence: 99%